Understanding environmental pollution - Hill, Marquita K. (Cambridge : Cambridge University Press, 2010)
Starting with the definition of pollution and how pollutants behave, this text progresses to covering air and water pollution basics, pollution and global change, solid waste, and pollution in the home.
Include bibliographical and index.
Keywords: Environmental pollution